Students' and staffs' views and experiences of asymptomatic testing on a university campus during the COVID-19 pandemic in Scotland: a mixed methods study. Issue 3 (20th March 2023) - Bauld, Linda; Street, Alice; Connelly, Roxanne; Bevan, Imogen; Morlet Corti, Yazmin; Baxter, Mats Stage; Stagg, Helen R; Christison, Sarah; Mulherin, Tamara; Sinclair, Lesley; Aitman, Tim
Abstract : Objectives: To explore the acceptability of regular asymptomatic testing for SARS-CoV-2 on a university campus using saliva sampling for PCR analysis and the barriers and facilitators to participation. Design: Cross-sectional surveys and qualitative semistructured interviews. Setting: Edinburgh, Scotland. Participants: University staff and students who had registered for the testing programme (TestEd) and provided at least one sample. Results: 522 participants completed a pilot survey in April 2021 and 1750 completed the main survey (November 2021). 48 staff and students who consented to be contacted for interview took part in the qualitative research. Participants were positive about their experience with TestEd with 94% describing it as 'excellent' or 'good'. Facilitators to participation included multiple testing sites on campus, ease of providing saliva samples compared with nasopharyngeal swabs, perceived accuracy compared with lateral flow devices (LFDs) and reassurance of test availability while working or studying on campus. Barriers included concerns about privacy while testing, time to and methods of receiving results compared with LFDs and concerns about insufficient uptake in the university community. There was little evidence that the availability of testing on campus changed the behaviour of participants during a period when COVID-19 restrictions were in place. Conclusions: The provision of free asymptomatic testing for COVID-19 on a university campus was welcomed by participants and the use of saliva-based PCR testing was regarded as more comfortable and accurate than LFDs. Convenience is a key facilitator of participation in regular asymptomatic testing programmes. Availability of testing did not appear to undermine engagement with public health guidelines.